2009
DOI: 10.1111/j.1742-4658.2009.07057.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic characterization of lipid raft proteins in amyotrophic lateral sclerosis mouse spinal cord

Abstract: Familial amyotrophic lateral sclerosis (ALS) has been linked to mutations in the copper/zinc superoxide dismutase (SOD1) gene. The mutant SOD1 protein exhibits a toxic gain‐of‐function that adversely affects the function of neurons. However, the mechanism by which mutant SOD1 initiates ALS is unclear. Lipid rafts are specialized microdomains of the plasma membrane that act as platforms for the organization and interaction of proteins involved in multiple functions, including vesicular trafficking, neurotransmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 66 publications
(83 reference statements)
5
51
1
Order By: Relevance
“…Recently, proteomic analysis demonstrated that membrane SOD (SOD1) is present in LR fractions (441), a fact consistent with previous reports that SOD1 is detectable in LRs (351). Reported SOD1 levels, for example, in LRs fractions were much higher than that in other areas of the plasma membrane.…”
Section: B Superoxide Dismutasesupporting
confidence: 86%
See 1 more Smart Citation
“…Recently, proteomic analysis demonstrated that membrane SOD (SOD1) is present in LR fractions (441), a fact consistent with previous reports that SOD1 is detectable in LRs (351). Reported SOD1 levels, for example, in LRs fractions were much higher than that in other areas of the plasma membrane.…”
Section: B Superoxide Dismutasesupporting
confidence: 86%
“…These results support the view that in aggregation the LRs may play an important role for the SOD1 actions (6,201). It is assumed that localization and subsequent aggregation of SOD1 in LRs could affect cellular functions as well as the interplay between different cell types, as LRs are rich in receptors and the signaling molecules necessary for cell-cell communications (441). Indeed, a more recent study has reported that H 2 O 2 , generated extracellularly by extracellular SOD, anchored to ECs surface via the heparin-binding domain (HBD), enhances VEGF-induced VEGF receptor 2 (VEGFR2) autophosphorylation in caveolin-enriched LRs, but not in noncaveolar LRs.…”
Section: B Superoxide Dismutasesupporting
confidence: 83%
“…Immobilization, disuse or denervation triggers muscular atrophy, which clearly shows that neuromuscular innervation patterns are directly linked to gene expression, protein abundance and isoform patterns in skeletal muscles [29]. In analogy to the recent proteomic profiling of cerebrospinal fluids from patients suffering from ALS and the spinal cord from the wobbler mouse [19][20][21][22][23], this study describes the findings of the MS-based proteomic survey of skeletal muscle from the WR mouse. From the detailed analysis of the isoform patterns of the sarcomeric MyHCs it became clear that the response of gene expression in skeletal muscle to denervation is characteristically different from that to hyper-excitability and muscular dystrophy [28].…”
Section: Resultsmentioning
confidence: 97%
“…Expression levels were reduced in the case of 3 protein species and increased for 21 proteins. The mass spectrometric hit with the highest increase of 6.5 relative concentration is not listed in Table 1 proteins spots which both represent fast myosin binding protein C (spots 23,24). In order to verify key proteomic findings and to put this study into perspective with previous analyses of WR muscle tissues, representative immunoblots are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation